Penetapan Kadar Flavonoid Total Ekstrak Etanol Buah Belimbing Wuluh (Averrhoa Bilimbi L.) Dengan Metode Spektrofotometri Uv-Vis - Anita Agustina Styawan; Muchson Arrosyid; Hendra Budiman; Choiril Hana Mustofa; Anna Latifah (Universitas Muhammadiyah Klaten, 2024)
Star fruit is a fruit that has been cultivated for a long time by Indonesian people. Star fruit plants consist of two types. Sweet starfruit and sour starfruit or wuluh, starfruit can be used as an anti-inflammatory and antioxidant. So further research needs to be carried out on testing the flavonoid content of ethanol extract of star fruit (Averrhoa bilimbi L.) using the UV-Vis spectrophotometric method. So that the potential for developing this plant as a medicinal ingredient for the prevention and treatment of various diseases can be increased. The aim of this study was to determine the levels of flavonoids in star fruit. This study used a sample of 3 kg of star fruit. Extraction using the maceration method with 96% ethanol solvent. Then analyzed qualitatively and quantitatively. The results of the research showed that the qualitative test with color reagents showed positive results of a brownish yellow color, there were flavonoid compounds in the star fruit, while the results of the quantitative test with UV- Vis spectophotometry showed levels of flavonoid compounds with an average of 0.4384% w/w or 4,384 mg/kg.